Sleep Bruxism and SDB in Albanian Growing Subjects: A Cross-Sectional Study - Giuseppina Laganà; Vesna Osmanagiq; Arianna Malara; Nicolò Venza; Paola Cozza (MDPI AG, 2021)
The aim of this study was to evaluate a possible correlation between sleep bruxism and risk factors of developing obstructive sleep apnea syndrome (OSAS) in a sample of growing subjects and to assess parental awareness about sleep bruxism in their children. Methods: The sample was composed of 310 subjects (173 females and 137 males), with a mean age of 8.9 years, attending "Ndre Mjeda" school of Tirana (Albania). All parents of the children participating in the study were asked to fill in a questionnaire manually or via a digital version. The questionnaire was composed of three sections: personal data, sleep quality data, and OSAS risk factors, and it was filled out by both parents. Results: Of our samples, 41.3% presented with bruxism, and 16.5% of the parents ground their teeth. Oral breathing was reported in 11.9% of the subjects, and among these, 40% of the subjects were affected by bruxism (p > 0.05). Of the subjects, 18.7% snore overnight. Comparing it with sleep bruxism, the two phenomena are often related (p = 0.00). Conclusions: Heredity, night-sweating, nycturia, oral breathing, and snoring seem to have a significant correlation with bruxism.